A novel pipeline leak detection and localization method based on the FBG pipe-fixture sensor array and compressed sensing theory. (15th April 2022) - Wang, Jiajian; Ren, Liang; Jia, Ziguang; Jiang, Tao; Wang, Guo-xin
Highlights: A novel pipeline leak localization method is presented without solutions of the arrival time difference of NPW knee point. The localization accuracy of the presented method can be improved without increasing number of sensors. A novel FBG pipe-fixture sensor is developed to measure pressure variations in NPW signals. A coefficient bCS is proposed to determine the optimal localization accuracy. The presented method has excellent localization stability. Abstract: Low localization accuracy and instability have always been two primary problems for the pipeline leak detection and localization method based on the negative pressure wave (NPW) technique. In this paper, based on compressed sensing (CS) theory, a novel pipeline leak detection and localization method is proposed to replace the solutions of the arrival time difference of NPW knee points. In addition, based on the presented method, the localization accuracy can be improved without increasing the number of sensors. To validate the localization accuracy and stability of the presented method, a pipeline leak simulation test under flow conditions is conducted on a steel pipe leak test platform. The fiber Bragg grating (FBG) pipe-fixture sensor array is developed and applied to detect pipeline leakage and measure the pressure variations in the NPW signals, which provides the data basis for pipeline leak localization based on CS theory. A concept of the relative localization coefficient b CS is proposed, and the test results indicate that when b CS is 0.5, all localization errors of different leakage points with different leakage rates are 2 m.